An innovative environmental citizen behavior model: Recycling intention as climate change mitigation strategies. (1st October 2019) - Yu, Tai-Kuei; Lin, Feng-Yi; Kao, Kai-Yun; Chao, Cheng-Min; Yu, Tai-Yi
Abstract: Climate change has been led to the increasing magnitude of frequency and severity of extreme weather, causing serious damage to overall economy of a country and individual economy of enterprises. Only relying on government subsidy to combat the impact of climate change, the work could be in vain. This study tries to use recycling action as mitigation strategies of climate change, and analyze the dominant influencing factors that affect recycling intention. This study stands in the perspective of green education in universities, regards the recycling intentions in response to climate change as pro-environmental behaviors, and revises and verifies the citizen pro-environmental behavior model. The green educations programs can communicate, promote, active and internalize the environmental citizenship through resource recycling intentions. Students learn about the importance of advocacy and activism to environmental citizenship, then generate environmentally sustainable and recycling intentions, and achieve the goal of improving the environment and mitigating to climate change. Graphical abstract: Image 1 Highlights: Exploring the determinants of recycling intention to mitigate climate change is a complex task. The NEP values are conceptualized as connectedness to nature and environmental concerns constructs. The advocacy and activism are viewed as adopting environmental citizenship behaviors. Under the NEP, connection to nature and environmental concern affect individual to become an advocate. The ECBOs and ECBIs significantly support advocacy and change recycling intentions.